Primary Stromal Breast Sarcoma with Concomitant Contralateral Carcinoma: A Rare Case from Syria - Rawan Al khudari; Mohannad Homsi; Hasan Al zohaily; Maher S. Saifo (Case Reports in Oncological Medicine)
Bilateral breast cancers are rare cases encountered and are usually the same type in both sides. Only very few cases were reported to have different histological types of neoplasia involving sarcoma. Moreover, sarcomas rarely originate from the breast as a primary lesion whereas the common presentation is having angiosarcoma following radiotherapy. In this report, we present a rare case of a Syrian 43-year-old woman having two distinct primary lesions in the breasts: invasive ductal carcinoma and contralateral stromal sarcoma.